2010
DOI: 10.3109/13668250.2010.517189
|View full text |Cite
|
Sign up to set email alerts
|

Staff members' understandings about communication with individuals who have multiple learning disabilities: A case of Finnish OIVA communication training

Abstract: The findings of this study suggest that it is important to give staff members the opportunity to learn new practices and to explore the thinking that underpins the actions they perform during communication training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…One reason for this discrepancy may be that it was difficult to assess from the interviews alone whether the teachers' descriptions of consistent use of KWS concerned intended or realized use of KWS. Another reason may be that these teachers and therapists had different views on what constituted consistent use of KWS (Koski, Martikainen, Burakoff, & Launonen, 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
See 1 more Smart Citation
“…One reason for this discrepancy may be that it was difficult to assess from the interviews alone whether the teachers' descriptions of consistent use of KWS concerned intended or realized use of KWS. Another reason may be that these teachers and therapists had different views on what constituted consistent use of KWS (Koski, Martikainen, Burakoff, & Launonen, 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…For example, researchers may discuss video-recordings of naturalistic practice with staff, to gather in-depth information on participants' experiences and views. Because the views of various team members may differ (Calculator, 1999;Dietz, Quach, Lund, & McKelvey, 2012;Koski et al, 2010), including the entire team in such discussions offers an interesting prospect.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Moreover, the findings regarding increased self‐efficacy to use communication strategies are in keeping with previous research. For instance, Koski et al () found that training resulted in changes in staff members’ thinking habits concerning adults with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence for VRT’s effectiveness for training communication skills of staff that support adults with learning disabilities within residential care settings. Koski, Martikainen, Burakoff, and Launonen () evaluated the effectiveness of VRT in combination with other training techniques and reported effectiveness for training outcomes including trainees’ self‐reports of change and thinking habits. Bloomberg, West, and Iacono () showed improvements in staff members’ communicative ability and the impact of this on their client's behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The definition also draws on research exploring interactions between people with intellectual disabilities and their communication partners (e.g. McNaughton and Light 1989, McConkey et al 1999, Bradshaw 2001, Hostyn and Maes 2009, Koski et al 2010). Similarly to Habermas’ (1984) theory of communicative action, this definition does not aim to define the best communication in a given context, but gives a starting point for which to aim.…”
Section: Introductionmentioning
confidence: 99%